Caribbean Report 14-09-1988 - Whitehorne, Pat (anchor); O'Toole, Pamela (correspondent); Martin, Lionel (correspondent); Crosskill, Hugh (correspondent); Golding, Bruce (interviewee); Edwards, Andy (correspondent); Simpson, Judy (interviewee) (The British Broadcasting Corporation, 1988)
The program provides an update on Hurricane Gilbert as it devastated Jamaica and Cayman Islands, and moves towards Mexico. Relief operations are underway in Jamaica and the United Nations appeals for aid in post-Gilbert Jamaica. Secondly, the expulsion of Cuban officials from Britain reiterates Cuba’s position that the incident was the result of a bungled CIA MI5 operation. Thirdly, the brutal attacks on two churches in Haiti and a raid on an independent radio station prompted the National Coalition for Haitian Refugees based in US to write to the US Secretary of State about the recent spate of violence in Haiti. The report also features an interview with Bruce Golding, Chairman of Jamaica’s ruling Labour Party, on the government’s success in reducing Jamaica's ganja production from 15,000 tons in 1986 to approximately 300 tons in 1988. It concludes with a brief interview with Judy Simpson, Jamaican-born heptathlete, at a training camp near Tokyo in her preparation for the Seoul Olympics.
1. Headlines (00:00-00:35)
2. Hurricane Gilbert in Jamaica (00:36-04:24)
3. Expulsion of Cuba's Ambassador to Britain (04:25-06:22)
4. Financial News (06:23-07:50)
Keywords: Hurricanes -- Jamaica.; Hurricane Gilbert, 1988.; Ambassadors -- Cuba -- Expulsion.; Violence -- Haiti.; Marijuana -- Jamaica.; Jamaica Labour Party.; Olympic athletes -- Jamaica.; Heptathlon -- Jamaica.; Ganja -- Jamaica.; Azpillaga, Florintion.; Medina, Carlos.; National Coalition For Haitian Refugees.; Simpson, Judy.